Pelatihan Pengolahan Dan Transformasi Data Otomatis Berbasis N8N Pada SMK Kabupaten Cirebon - Saeful Anwar; Dadang Sudrajat; Muhamad Ilham Nur Faqih; Firman Yudatama (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This Community Service Activity raised the theme "n8n-Based Automatic Data Processing and Transformation Training at Vocational High Schools in Cirebon Regency." The activity was held on Saturday, April 4, 2026, targeting participants from the Cirebon Regency Vocational High School environment. This program was motivated by the need for vocational schools to improve data management capabilities, utilize digital technology, and automate work processes. School activities generate a lot of data, such as student data, attendance, activity registration, grades, evaluation questionnaires, and administrative reports. This data is often managed manually, spread across various media, and requires a long time to be summarized. The solution provided was training in automatic data processing and transformation using n8n. n8n was chosen because it has a visual interface, supports the low-code concept, can connect various applications, and allows users to build automated workflows gradually. The implementation method uses a participatory, educational, practical, problem-based, and sustainable approach. The activity began with partner coordination, module development, technical preparation, workshop implementation, guided practice, case studies, evaluation, and follow-up recommendations. The results of the activity showed that participants gained an understanding of data concepts, data transformation, workflow automation, triggers, nodes, outputs, and workflow evaluation. Participants were also able to create simple workflows based on school case studies, such as activity registration recaps, attendance processing, automatic notifications, and evaluation recaps. The participant satisfaction evaluation showed an average score of 4.48, categorized as very satisfied. The training benefits and practical methods indicators received high scores, thus the training was deemed relevant to the school's needs. Overall, this activity successfully improved digital literacy, basic data automation skills, and participants' awareness of the importance of technology-based work efficiency. This program is expected to serve as a foundation for the development of data automation in vocational schools in Cirebon Regency and support the sustainable digital transformation of vocational education.